DISPARITAS PUTUSAN HAKIM DALAM DALUARSA GUGATAN PHK PADA PENGADILAN HUBUNGAN INDUSTRIAL: Disparity in Judges' Decisions in the Expiration of Termination Lawsuits at the Industrial Relations Court - Andari Yuriko Sari; Sugeng Santoso PN; Amriyati; Adiasih, Ning; Gabriel Bramantyo Utomo (Jurnal Hukum PRIORIS, 2024)
Initially in the Legislative Regulations, Article 82 of Law Number 2 of 2004 concerning Settlement of Industrial Relations Disputes should have been the legal basis used by the judge in deciding the case. Article 1969 of the Civil Code stipulates that the expiration period for cases of employment termination is 2 years. Changes occurred later where Law Number 06 of 2023 concerning Ratification of Government Regulations in Lieu of Law Number 2 of 2022 concerning Job Creation became law removing articles related to expiration, namely Article 89 and Article 171. Constitutional Court Decision Number 94/even later decided that the expiration period would only last one year. Various changes to statutory regulations governing changes in regulations regarding the expiration date for filing a lawsuit at the Industrial Relations Court have actually been discussed in several national journal articles in Indonesia, but the impact on filing lawsuits and the results of decisions at the Industrial Relations Court ultimately creates legal uncertainty for the parties. The formulation of the problem in this paper is how judges in their judgment assess whether a lawsuit in the Industrial Relations Court has or has not expired and how the disparity in Industrial Relations Court decisions in terms of expiration affects legal certainty regarding the expiration of the lawsuit.